Operation and Maintenance Operational Management Application for Building Facilities Based on Android: Operation and Maintenance Operational Management Application for Building Facilities Based on Android - Ahmad Avivanto; Agung Triayudi; Ira Diana Sholihati (Institute of Computer Science (IOCS), 2020)
Application is a program created to do and carry out special tasks from the user. The computer system program in the form of an android-based application can be used in various fields, one of which is in the property as the operational management of building engineering in carrying out maintenance and inspection of building facilities. This Android-based application research aims to increase productivity and make it easier to carry out operational tasks, ensuring the operational integrity of building stationary equipment. The method for software development uses the SDLC (System Development Life Cycle) model, which is a method that describes the process of developing information systems. The problem obtained from the research is the management data processing which is still using manual or written so that the data received by the operational technician is inaccurate because the addition of the data is slow and to search for the data is too difficult because the data stored is hardcopy too much. The suggestion in proposing an android-based application system that assigns applications to the user is accessing the menu contained work orders in conducting a checklist to maintain and analyze building facilities. With this android-based application for operational engineering, you can enjoy the convenience of carrying out operational tasks and the data obtained can be stored so that it can be easily found or viewed at any time to be evaluated for damage to building facilities.